TRIGA-SPEC: the prototype of MATS and LaSpec. (March 2015) - Kaufmann, S; Beyer, T; Blaum, K; Block, M; Düllmann, Ch E; Eberhardt, K; Eibach, M; Geppert, C; Gorges, C; Grund, J; Hammen, M; Krämer, J; et al.
Abstract: Investigation of short-lived nuclei is a challenging task that MATS and LaSpec will handle at the low energy branch of Super-FRS at FAIR. The groundwork for those experiments is laid-out already today at the TRIGA-SPEC facility as a powerful development platform located at the research reactor TRIGA Mainz. The latest status, new developments and first results of commissioning runs are presented here.